PENGARUH PERBEDAAN BAGIAN TANAMAN TERHADAP KADAR TOTAL FENOLIK DAN KADAR TOTAL FLAVONOID EKSTRAK TALAS (Colocasia esculenta L) - Laksmi RAMAYANI, Septiana; Putri SANDIYANI, Riska; Oktaviani DINASTYANTIKA, Vavi (Media Farmasi Indonesia, 2020)
The Taro plants (Colocasia esculenta L) consist of leaves, stalk, and tubers that have pharmacological activity. There are the healing of wounds and antioxidant activity because of the containing of phenolic and flavonoid compounds. Activity pharmacology of various plant parts taro influenced by the active substance contained in each part of a plant that produces differences of activity pharmacology. The purpose of the research is to know the influence of parts of an organ plant on the total phenolic and the total flavonoid plant extracts taro. The extraction method used Microwave-Assisted Extraction (MAE) with 96% ethanol. An extract obtained determined the total phenolic with the methods Folin-ciocalteau using gallic acid as standard while levels flavonoid determined by the addition of reagent AlCl3 using Quercetin as a standard. Total phenolic content and total flavonoid content measured the use of the spectrophotometer UV-Vis. This research result indicates that the differences part of a plant significantly affected the total phenolic and flavonoid plant extracts taro. The highest levels of total phenolic and flavonoid there are on the leaves of taro plants